Learning and teaching through inquiry with geospatial technologies: A systematic review - Vendula Mašterová (European Journal of Geography)
The development of digital skills among pupils at the lowest levels is already an important part of education. The implementation of geospatial technologies (GST) is one of the ways to build and deepen these skills in primary and secondary schools. The use of these technologies is possible through an inquiry approach. This paper aims to identify the knowledge gaps on the issue of linking GST and inquiry in primary and secondary school learning and teaching. This article presents findings from 36 English-language empirical research studies published up to 2020 in the Web of Science and Scopus databases. The systematic review focuses mainly on the methods used and the results of the studies. The analysis of the studies shows that the methods used are strongly heterogeneous, and qualitative and quantitative methods are similarly represented. The results of the studies indicate that prior teacher preparation is necessary for this type of learning and teaching,  and that students develop digital competencies and knowledge related to GST and the topic of the learning task that is addressed using these technologies. This systematic review presents recommendations and pitfalls for learning and teaching through inquiry with GST, but also recommendations for future research.